2020
DOI: 10.5294/edu.2020.23.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Análisis bibliométrico de estudios sobre factores socioeconómicos en estudiantes universitarios

Abstract: El artículo presenta una actualización de las variables socioeconómicas relacionadas con el abandono de los estudios universitarios. Se utilizó la metodología del metaanálisis, a partir de la revisión sistemática de estudios científicos relacionados con el tema. De 143 artículos publicados en el período 2005-2019, se seleccionaron 71 que cumplieron plenamente con los criterios de selección de la muestra: relación directa con la temática del estudio, publicados en revistas en español del área de educación e ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Studies on this type of variable were divergent, as there are two trends. The first indicates that socio-economic variables do not influence dropout in higher education (e.g., [51,52]), which gives greater relevance to other determinants to explain the dropout event [53]. The second indicates which of these socio-economic variables contribute directly to dropout in concordance with those of the other determinants [53].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on this type of variable were divergent, as there are two trends. The first indicates that socio-economic variables do not influence dropout in higher education (e.g., [51,52]), which gives greater relevance to other determinants to explain the dropout event [53]. The second indicates which of these socio-economic variables contribute directly to dropout in concordance with those of the other determinants [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, financial insecurities stemming from the student's unstable job may lead to non-completion of studies [56]. Regarding research that relates the variable of social stratum, understanding this as a classification of the property or dwelling occupied by the student and their family that accounts for the socioeconomic condition of these, the employment situation, the economic income of the family nucleus and the student, showed that students with lower income levels have several disadvantages when entering higher education, given that the accumulated social and cultural capital is usually lower than that of people with higher incomes [53], which directly influences the academic determinant variables that can lead students to drop out.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the economic approach has privileged the socioeconomic context of the student and his or her family by evaluating the cost-benefit ratio of staying or dropping out of higher education (Palacio et al, 2020), the influence of family income on the probability of not completing the educational process (Adrogué and García de Fanelli, 2018), social class as a constraint to the creation of social capital (Palacio et al, 2020), among others. While most studies have focused on the student and the family, they have also assessed the impact of the drop-out event on the operational income of HEIs and their financial sustainability (Barragán and Rodríguez, 2015).…”
Section: Dropout and The Theoretical Reference Modelmentioning
confidence: 99%
“…Faced with the multi-causality of dropout, efforts have been made to establish the variables that explain current dropout rates and the causes that lead students not to complete their higher education studies, which has resulted in various perspectives and the development of tools that allow decision-makers to have a holistic view of dropout prevention and mitigation (Kehm et al, 2019). That said, research has focused on analysing the influence of specific variables on the materialisation of dropout based on individual student conditions such as age, gender, marital status, family environment, intrinsic motivations and academic selfregulation (e.g., Ghignoni, 2017;Arias-Velandia et al, 2018;Behr et al, 2020); the student's socioeconomic background exemplified by the socioeconomic stratum of the dwelling he or she lives in, family income, economic dependency and the macro-economic environment of the country (e.g., Contreras, 2017;Behr et al, 2020;Palacio et al, 2020;Schmitt et al, 2020); the academic factors represented in the development of competencies prior to entry into higher education, secondary school graduation tests, levels of satisfaction in the training programme and the number of courses concurrently taken (e.g., Guzmán, et al, 2020a;Heidrich, 2018); and finally, institutional circumstances in relation to HEI policies, the technological and pedagogical resources provided by the educational institution, the level of interaction with teachers and students and the pedagogical model (e.g., Armstrong et al, 2018;Choi and Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los principios que manifiesta la Ley Universitaria es el interés superior del estudiante (Ley Universitaria -Ley 30220, 2014), muchas de las actividades que emprende la Universidad y los Programas Académicos que la componen se han focalizado en este principio procurando satisfacer las necesidades educativas de los estudiantes en las aulas universitarias (Ruiz y Manrique, 2016); sin embargo desde la llegada de la pandemia por SARS-CoV-2 ha originado un retraso en el avance que se venía realizando, provocando cambios abruptos en las formas de enseñanza en la universidad (Guarnizo, 2021). Sobre todo, porque los estudiantes ya no tienen acceso a los recursos tecnológicos que se encuentran en las universidades, como son los equipos de cómputo, equipos de laboratorio, bibliotecas y servicio de internet gratuito, que permitía desarrollar con normalidad sus competencias académicas, estando muchos lejos de estos servicios se han visto perjudicados, incluso han abandonado los estudios por la precariedad en la que se encuentran (Palacio et al, 2020;Pequeño et al, 2020).…”
Section: Introductionunclassified